An optimized secretory expression system and immunogenicity evaluation for glycosylated gp90 of avian reticuloendotheliosis virus - Qing Pan; Jing Wang; Altaf Hussain; Yulong Gao; Hongyu Cui; Kai Li; Xiaole Qi; Changjun Liu; Yanping Zhang; Shide Zhang; Xiaomei Wang (Veterinary Research, 2020)
Abstract Reticuloendotheliosis is an important immunosuppressive disease, associated with avian reticuloendotheliosis virus (REV) infection, and causes notable economic losses worldwide. Glycoprotein gp90 is an important structural protein of REV, and considered to be the most important immunogenic antigen, which can induce neutralizing antibodies against REV. In this study, an optimized suspension culture system was developed and applied to secretory express the immunogenic surface antigen gp90. To achieve an optimal glycosylation, the gp90 was designed to secretory expressed into the supernatant of the cell culture, which also occurs in the natural protein maturation procedure of REV. Serum-free culture medium was introduced to simplify the purification process and reduce the production costs. Based on the purified glycosylated gp90, an oil-emulsion subunit REV vaccine candidate was developed and evaluated in chickens. The subunit gp90-based vaccine induced fast immune responses, high levels of antibodies (REV-specific antibody, gp90-specific antibody, and neutralizing antibody against REV), and preferential T helper 2 (Th2) (interleukin-4 secretion) not Th1 (interferon-γ secretion) response. Furthermore, the viremia induced by REV infection was significantly reduced in chickens immunized with the glycosylated gp90. Overall, an optimized secretory expression system for glycosylated gp90 was developed, and the glycosylated gp90 obtained in this study retained good immunogenicity and could be an attractive vaccine candidate to protect chickens against REV horizonal infection.